Legal and ideological model of the formation of socio-legal consciousness of military servicemen as a component of social and legal support of the activities of the personnel of the national guard of Ukraine - Midina, Anastasia; Orel, Oksana (ScienceRise: Juridical Science, 2022)
The article is devoted to a comprehensive study of the social and legal support of the military personnel of the National Guard of Ukraine. During which it was found out that, according to the norms of the current legislation, social and legal support is an activity to create the necessary social and legal conditions for observing constitutional rights and freedoms, meeting the social needs and interests of military personnel in the course of preparing and performing combat missions; compliance with international humanitarian law; maintaining high discipline, organization and order. Based on this, the author's vision of the factors, influencing the formation of the social and legal consciousness of military personnel during military service and performing tasks for their intended purpose, is formulated, and three levels of their implementation are defined: micro-level, medium level and macro-level. The micro level includes: basic knowledge (obtained at school, higher educational institutions, higher military educational institutions); safety conditions in the performance of service and combat missions (norms of the current legislation); socio-cultural development (the degree of development of a serviceman in all spheres of human activity under the influence of changes in the dominant system of values). Medium level – self-realization (realization of the potential of a serviceman through career achievements); qualification of the military team/chief (formed by the personal attitude of the team/chief to the legal norms of the current legislation and implemented by observing them). Macro level – the mentality of society (way of thinking, general spiritual mood of society); state policy of Ukraine (the reaction of the state to specific problems of society (or groups in this society) is a fundamental guide to action for public authorities in accordance with laws and social customs). Based on the results of the study, the author's position on the very legal-ideological model of the formation of the social and legal consciousness of military personnel as a component of social and legal support for the activities of the personnel of the National Guard of Ukraine and its levels is provided. In order to increase the effectiveness of the functioning of the legal-ideological model for the formation of the social and legal consciousness of NGU military personnel, it is advisable: within the macro-level – the state leadership adhere to the implementation of social guarantees for military personnel and strengthen the propaganda of the authority of the "man in uniform" through the media; within the framework of the middle level – the local leadership independently make decisions on improving the quality potential of personnel, based on the specifics of the assigned tasks; within the framework of the micro level – during individual training, constantly inform the personnel about the latest changes in the current legislation and instill legal consciousness for the actions taken. Attention is focused on the problematic issues that arise at the present stage of development of the state